A Configurationally Confined Thermally Activated Delayed Fluorescent Two‐Coordinate CuI Complex for Efficient Blue Electroluminescence. Issue 7 (12th January 2023) - Wang, Hai‐Jie; Liu, Yuan; Yu, Baoqiu; Song, Shi‐Quan; Zheng, You‐Xuan; Liu, Kanglei; Chen, Pangkuan; Wang, Hailong; Jiang, Jianzhuang; Li, Tian‐Yi
Abstract: Thermally activated delayed fluorescence (TADF) from linear two‐coordinate coinage metal complexes is sensitive to the geometric arrangement of the ligands. Herein we realize the tuning of configuration from coplanar to orthogonal gradually by variation of substituents. In a complex with confined twist configuration, its blue emission peaking at 458 nm presents a high ΦPL of 0.74 and a short τTADF of 1.9 μs, which indicates a fast enough k r, TADF of 3.9×10 5 s −1 and a depressed k nr of 1.4×10 5 s −1 . Such outstanding luminescent properties are attributed to the proper overlap of HOMO and LUMO on Cu I d orbitals that guarantees not only small Δ E ST but also sufficient transition oscillator strength for fast k r, S 1 k_r, S_1 . Vacuum‐deposited blue OLEDs with either doped or host‐free emissive layer present external quantum efficiencies over 20 % and 10 %, respectively, demonstrating the practicality of the configurationally confined strategy for efficient linear Cu I TADF emitters. Abstract : Efficient thermally activated delayed fluorescent (TADF) two‐coordinate Cu I complex is designed by configurationally confined strategy. With proper twist angle around 45° between ligands, fast radiative decay is achieved with balanced Δ E ST and k r of S1, meanwhile, k nr is also depressed. As demonstrated in efficient OLED with high EQE over 20 % and small efficiency roll‐off less than 2 %, configurationally confined strategy is practical for developing novel Cu I TADF emitters.